Colitis as a clinical manifestation of disseminated histoplasmosis in HIV-positive patient: a case report - Daniel Zaputra; Ni Made Dewi Dian Sukmawati; I. Wayan Juli Sumadi (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction Disseminated histoplasmosis is a systemic fungal infection resulting from co-infection in severely immunosuppressed patients, such as those with human immunodeficiency virus (HIV) or acquired immunodeficiency syndrome.